Mediation Effect of Suicide-Related Social Media Use Behaviors on the Association Between Suicidal Ideation and Suicide Attempt: Cross-Sectional Questionnaire Study - Liu, Xingyun; Huang, Jiasheng; Yu, Nancy Xiaonan; Li, Qing; Zhu, Tingshao (JMIR Publications, 2020)
BackgroundA limited number of studies have examined the differences in suicide-related social media use behaviors between suicide ideators and suicide attempters or have sought to elucidate how these social media usage behaviors contributed to the transition from suicidal ideation to suicide attempt. ObjectiveSuicide attempts can be acquired through suicide-related social media use behaviors. This study aimed to propose 3 suicide-related social media use behaviors (ie, attending to suicide information, commenting on or reposting suicide information, or talking about suicide) based on social cognitive theory, which proposes that successive processes governing behavior transition include attentional, retention, production, and motivational processes. MethodsWe aimed to examine the mediating role of suicide-related social media use behaviors in Chinese social media users with suicidal risks. A sample of 569 Chinese social media users with suicidal ideation completed measures on suicidal ideation, suicide attempt, and suicide-related social media use behaviors. ResultsThe results demonstrated that suicide attempters showed a significantly higher level of suicidal ideation (t563.64=5.04; P<.001; two-tailed) and more suicide-related social media use behaviors, which included attending to suicide information (t567=1.94; P=.05; two-tailed), commenting on or reposting suicide information (t567=2.12; P=.03; two-tailed), or talking about suicide (t542.22=5.12; P<.001; two-tailed). Suicidal ideation also affected suicide attempts through the mediational chains. ConclusionsOur findings thus support the social cognitive theory, and there are implications for population-based suicide prevention that can be achieved by identifying behavioral signals.